PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI - Nel Arianty (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
Organizational culture is a pattern of behavior developed by anorganization's employees learned when faced with problems of externaladaptation and internal integration, that has proven good enough to be approvedand taught to new members as a way to realize, think and feel. In addition,organizational culture refers to a system of shared meaning held by members thatdistinguishes the organization from other organizations. Organizational culturewithin an organization is usually associated with values, norms, attitudes andwork ethic on hold in common by each component of the organization. If theculture of the organization will be able to improve both the high performance andwill contribute to the company's success.